Persistent Liver Dysfunction in Pediatric Patients After Total Cavopulmonary Connection Surgery - Luo, Qipeng; Jia, Yuan; Su, Zhanhao; Wang, Hongbai; Li, Yinan; Wu, Xie; Liu, Qiao; Liu, Xiaoguang; Yuan, Su; Yan, Fuxia (Frontiers in Cardiovascular Medicine, 2022)
Background Studies have reported early liver dysfunction (LD) after cardiac surgery is associated with short and long-term mortality. In this study, we aimed to investigate risk factors for persistent LD after total cavopulmonary connection (TCPC) surgery. Methods This is a retrospective case-control study. We defined persistent LD as LDs occurring between postoperative day 1 (POD1) and POD7 and sustaining at least on POD7, while transient LD as LDs occurring between POD1 and POD7 and recovering at least on POD7. Multivariable logistic regression analysis was applied and central venous pressure (CVP) was considered continuously or in quantiles. Results Postoperative LD occurred in 111 (27.1%) patients. Transient and persistent LD occurred in 65 (15.9%) and 46 (11.2%) patients, respectively. Aortic cross-clamping (ACC) (odds ratio [OR] 2.55, 95% CI 1.26–5.14) and postoperative CVP (OR 1.34, 95% CI 1.18–1.51) were risk factors for persistent LD, also identified for postoperative any LD and transient LD. Adding postoperative CVP to the model only including ACC significantly improved persistent LD prediction (△AUC 0.15, p = 0.002). Compared with CVP ≤ 14 mmHg, adjusted ORs and 95% CI of persistent LD for CVP of 14–16 and >16 mmHg were 3.11 (1.24, 7.81) and 10.55 (3.72, 29.93), respectively. Patients with persistent LD might have a longer length of mechanical ventilation (mean difference, 13.5 h) and postoperative hospital stay (mean difference, 7 days), and higher postoperative costs (mean difference, 6.7 thousand dollars) compared to those with transient LD. Conclusions Intra-operative application of ACC and postoperative elevated CVP were independent risk factors for persistent LD in pediatric patients following TCPC surgery. Compared to patients with transient LD, patients with persistent LD might have a longer length of mechanical ventilation and postoperative hospital stay, and higher postoperative costs. We should pay more attention to patients with high postoperative CVP to prevent their persistent LD occurrence.